Mediastinal Pseudocyst and Cardiac Tamponade Due to Massive Pericardial Effusion in Pediatric Chronic Calcific Pancreatitis - Basu, Suprit; Bhatacharya, Mala; Das, Suman; Debnath, Bidyut; Sen, Sandip; Chatterjee, Anish (Journal of Pediatric Intensive Care, 2017)
A 7-year-old male patient with a history of recurrent abdominal pain over 1 year presented with cardiac tamponade due to massive pericardial effusion, which was percutaneously drained. Contrast-enhanced computed tomography revealed a large posterior mediastinal cyst and calcified, heterogeneous pancreatic parenchyma. Elevated amylase and lipase levels of the cyst fluid confirmed the diagnosis of pancreatic pseudocyst, which was treated with an octreotide infusion and Roux-en-Y cystojejunostomy. The child was discharged on pancreatic enzyme supplement and was asymptomatic on follow-up.
Keywords: chronic calcific pancreatitis; mediastinal pancreatic pseudocyst; cardiac tamponade; Roux-en-Y cystojejunostomy